2019
DOI: 10.3390/s19051080
|View full text |Cite
|
Sign up to set email alerts
|

Collision Detection and Identification on Robot Manipulators Based on Vibration Analysis

Abstract: Robot manipulators should be able to quickly detect collisions to limit damage due to physical contact. Traditional model-based detection methods in robotics are mainly concentrated on the difference between the estimated and actual applied torque. In this paper, a model independent collision detection method is presented, based on the vibration features generated by collisions. Firstly, the natural frequencies and vibration modal features of the manipulator under collisions are extracted with illustrative exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Traditional model-based detection methods in robotics are mainly concentrated on the difference between the estimated and actual applied torque. Min et al [ 20 ] have proposed a model independent collision detection method based on the vibration features generated by collisions.…”
Section: Contributionsmentioning
confidence: 99%
“…Traditional model-based detection methods in robotics are mainly concentrated on the difference between the estimated and actual applied torque. Min et al [ 20 ] have proposed a model independent collision detection method based on the vibration features generated by collisions.…”
Section: Contributionsmentioning
confidence: 99%
“…In literature, different strategies based on FEM and experimental procedures to estimate NFs in robots have been presented [ 15 , 16 , 17 , 18 ]. FEM is the most used experimental procedure for vibration measurements integrated with signal processing techniques because it can estimate the real behavior of robots [ 19 , 20 , 21 , 22 , 23 , 24 ]. Although FEM provides results that are very close-to-real [ 25 ], it is necessary to perform an experimental validation of the behavior of the robot to identify the NFs with accuracy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although FEM provides results that are very close-to-real [ 25 ], it is necessary to perform an experimental validation of the behavior of the robot to identify the NFs with accuracy [ 26 ]. An important step of the experimental procedure is the use of a signal processing technique to estimate the NFs of robots [ 22 ]. In this regard, Fourier-based methods [ 19 , 20 , 21 , 22 , 23 ] and wavelet transform (WT) [ 24 , 27 ] have been the most commonly employed methods for performing this task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable robots to act in unstructured environments and physically interact with humans, collision detection was used, and some application examples were highlighted. Min et al [34] presented a collision detection method based on the vibrations caused by collisions. A BP neural network was used to analyze the vibration signals, and the experiments showed that detection could be realized by the frequency-domain and timedomain features of collision.…”
Section: Introductionmentioning
confidence: 99%